Resin-supported nanoiron: A powerful tool for heavy metal decontamination - Elucidating the mechanism through column studies - Mystrioti, Christiana; Papassiopi, Nymphodora; Xenidis, Anthimos (Technical Annals, 2024)
The significance of removing heavy metal ions from wastewater treatment plant effluents cannot be overstated in preserving a clean environment and protecting human health. Various methods, including adsorption, membrane-based processes, chemical treatments, electrical methods, and photocatalysis, have been documented for the effective removal of heavy metal ions from different wastewater sources. Nanoparticles, with their strong affinity, show promise in wastewater treatment, particularly in efficiently extracting heavy metals. This study aimed to evaluate the effectiveness of an iron nanocomposite, RnFe, in eliminating various heavy metals from effluents of wastewater treatment plants through column tests. RnFe is composed of iron nanoparticles supported in an inert cationic resin, produced using green tea extract as a reducing agent for Fe(III) to Fe(0). The introduced feed solution to the columns contained a mixture of heavy metals, including Cr(VI), As, Ni, Pb, Cu, Cd, and Zn. The study investigated the impact of contact time on the sorption and reduction rates of the selected compounds, varying contact times to 2.4, 4.8, and 6 minutes. RnFe demonstrated high efficiency in removing Cr(VI) and As, with effluent concentrations meeting environmental limits when the contact time exceeded 5 minutes. However, the performance of RnFe was less effective for divalent metal contaminants due to the strong competitive effect of coexisting Ca. The study provided a succinct exploration of the mechanisms involved in using the RnFe nanocomposite for the removal of metals and metalloids.